1979
DOI: 10.1007/bf02533508
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of linoleic acid in the cat

Abstract: Cats fed a diet containing linoleate as the only polyunsaturated fatty acid showed extremely low levels of arachidonate in the plasma lipids, as well as an increase in linoleate, eicosadienoate and an unknown fatty acid. Administration of [1-14C]linoleic acid and [2-14C]eicosa-8,11,14-trienoic acid to cats showed that in the liver there was no conversion of the [1-14C] 18:2 to arachidonate, whereas there was significant metabolism of [2-14C] 20:3 to arachidonate. It was found when methyl-gamma-linolenate was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
3

Year Published

1982
1982
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 14 publications
2
48
0
3
Order By: Relevance
“…Deficiencies in fatty acyl desaturase activities have precedents in terrestrial carnivores such as cats in which Δ6 and Δ5 desaturase activities may both be very low (35)(36)(37)(38). It has been hypothesized that this situation may be an evolutionary adaptation to carnivorous diets rich in preformed C 20 and C 22 HUFA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deficiencies in fatty acyl desaturase activities have precedents in terrestrial carnivores such as cats in which Δ6 and Δ5 desaturase activities may both be very low (35)(36)(37)(38). It has been hypothesized that this situation may be an evolutionary adaptation to carnivorous diets rich in preformed C 20 and C 22 HUFA.…”
Section: Discussionmentioning
confidence: 99%
“…This is now also known to be the case in cats. In early studies, a complete lack of Δ6 desaturation enzymatic activity in felines was originally reported in the literature (35)(36)(37)(38), although recent and more sensitive studies conducted with deuterated fatty acids, showed that a low level of Δ6 desaturase is present in the cat (39).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, results from in vivo studies with other marine fish species such as gilthead sea bream (Sparus aurata) and golden grey mullet (Liza aurata) were consistent with a deficiency in Δ5 desaturation [16,17]. Reduced flux through desaturase/elongase pathways due to reduced desaturase activities have precedents in terrestrial carnivores such as cats in which Δ6 and Δ5 desaturase activities may both be severely limited [18][19][20][21]. It was hypothesised that this situation may be an evolutionary response to differences in diet.…”
Section: Introductionmentioning
confidence: 68%
“…By contrast, diets containing 50g safflower oil plus 300 g hydrogenated beef tallow (6.7 % energy as linoleate)/kg prevented all clinical symptoms except reproduction problems in females (MacDonald et al 1983b). Workers in Australia (Sinclair et al 1979(Sinclair et al , 1981McLean & Monger, 1989) reported that cats maintained for up to 8 years on diets containing 50g safflower oilkg did not suffer the severe symptoms reported by Rivers and his colleagues (Rivers & Frankel, 1980). These cats appeared normal except for some dulling of hair coats and a general inability of females to produce more than two litters.…”
Section: Essential Fatty Acids In Cats: Lack Of A-6 Desaturationmentioning
confidence: 99%